War and peace : Alberico Gentili and the early modern law of nations - Vadi, Valentina (Legal history library. Studies in the history of international law ;, 2020)
"This treatise investigates the emergence of the early modern law of nations, focusing on Alberico Gentili's contribution to the same. A religious refugee and Regius Professor at the University of Oxford, Alberico Gentili (1552-1608) lived in difficult times of religious wars and political persecution. He discussed issues that were topical in his lifetime and remain so today, including the clash of civilizations, the conduct of war, and the maintenance of peace. His idealism and political pragmatism constitute the principal reasons for the continued interest in his work. Gentili's work is important for historical record, but also for better analysing and critically assessing the origins of international law and its current developments, as well as for elaborating its future trajectories."